Strategies for the selective loading of patchy worm-like micelles with functional nanoparticles. Issue 38 (21st September 2018) - Schöbel, Judith; Hils, Christian; Weckwerth, Anne; Schlenk, Mathias; Bojer, Carina; Stuart, Marc C. A.; Breu, Josef; Förster, Stephan; Greiner, Andreas; Karg, Matthias; Schmalz, Holger
Abstract : Patchy micelles are efficient templates for the regio-selective incorporation of nanoparticles, allowing the construction of tailor-made binary hybrids. Abstract : Block copolymer self-assembly in solution paves the way for the construction of well-defined compartmentalized nanostructures. These are excellent templates for the incorporation and stabilisation of nanoparticles (NPs), giving rise to highly relevant applications in the field of catalysis or sensing. However, the regio-selective incorporation of NPs in specific compartments is still an issue, especially concerning the loading with different NP types. Using crystallisation-driven self-assembly (CDSA), functional worm-like crystalline-core micelles (wCCMs) with a tailor-made, nanometre-sized patchy corona were prepared as versatile templates for the incorporation and stabilisation of metal and metal oxide NPs. Different strategies, like ligand exchange or co-precipitation of polymer stabilised NPs with one surface patch, were developed that allow the incorporation of NPs in specific regions of the patchy wCCM corona. Independent of the NP type and the incorporation method, the NPs showed no tendency for agglomeration and were fixed within the corona patches of the wCCMs. The binary loading of patchy micelles with metal and metal oxide NPs was realised by combining different loading strategies, yielding hybrids with homogeneously dispersed NPs guided by the patchy structure of the template.